User awareness of and satisfaction with online subscriptions of the Aklatang Emilio Aguinaldo, De La Salle University Dasmariñas - Samaniego, Sharon M.; Dela Torre, Nathalie N.; Ramos, Marian S. (Quezon City School of Library and Information Studies, University of the Philippines Diliman, 2009)
Libraries do not only provide their clientele with printed resources since there are available online subscriptions. This study was conceived in the light of the availability of these resources. Since libraries allocate a huge amount for access to online subscriptions, this study intended to find out the awareness and satisfaction of the Aklatang Emilio Aguinaldo's clientele specifically the students and faculty with the available online subscriptions which include e-journals.
Students from the first year to the fifth year level of the De la Salle University - Dasmarinas as well as its faculty members were the respondents of this study. Four hundred nineteen survey questionnaires have been accomplished.
To help assess the respondents' perceptions and use of the computer e-mail and the Internet, the Computer-Email-Web (CEW) Fluency Scale patterned from Bunz, 2001 was utilized. The twenty-item question included in Part C number 4 of the questionnaire was patterned from Dewald, N. H. & Silvius, M. A. (2005) which was able to determine the satisfaction of the respondents.
In relation to the awareness of online subscriptions, it was found out that 75 of the student respondents are not aware of the AEA's subscription to the EBSCOhost. The survey also revealed that 85 of the total student respondents are not aware of the online subscription, Emerald. As with the faculty members' awareness of EBSCOhost and Emerald, it was determined that 76 of the faculty members are not aware of the particular online subscriptions.
The data collected revealed the following findings: (1) there is a significant relationship between users' awareness on the availability of online subscriptions and their age, student's year level and users' college; (2) there is a significant difference in the awareness level of EBSCOhost and Emerald Management e-Journals among the respondents and their computer literacy as well as the type of database user; (3) there is a significant difference in the awareness level on the availability of EBSCOhost subscriptions among respondents by age; (4) there is a significant difference in the level of awareness on the availability of Emerald Management subscription and the gender of the respondents, the student respondent's year level and users' college; (5) there is a significant relationship between the respondents' satisfaction with both the online subscriptions and their gender, the type of database user, students' year level, and users' college; (6) there is a significant difference in the level of satisfaction with EBSCOhost subscription among respondents by gender; (7) there is a significant difference in the level of satisfaction with EBSCOHost and Emerald Management e-Journals subscription among respondents by type of database user students' year level and users' college.
Recommendations included enhancing promotion strategies for the online subscriptions and also conduct continuous training on the utilization of such resources.
Vita.
Special Problem (Master of Library and Information Science)
Keywords: Aklatang Emilio Aguinaldo, De La Salle University Dasmariñas; Electronic journal